2015
DOI: 10.1016/j.energy.2014.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Development of a model for the prediction of the fuel consumption and nitrogen oxides emission trade-off for large ships

Abstract: a model for the prediction of the fuel consumption and nitrogen oxides emission trade-off for large ships. Energy, 80, 545-555. DOI: 10.1016/j.energy.2014 Development of a model for the prediction of the fuel consumption and nitrogen oxides emission trade-off for large ships AbstractThe international regulations on fuel efficiency and NOx emissions of commercial ships motivate the investigation of new system layouts, which can comply with the regulations. In combustion engines, measures to reduce the fuel co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 33 publications
(40 reference statements)
0
22
0
Order By: Relevance
“…Coefficients (with 95% confidence bounds) for function (9) are: a = -1.968⋅10 5 (or alternatively -1.731⋅10 14 , 1.731⋅10 14 ), b = -0.001531 (or -131.3, 131.3), c = 1.968⋅10 5 (or alternatively -1.731⋅10 14 , 1.731⋅10 14…”
Section: Resultsmentioning
confidence: 99%
“…Coefficients (with 95% confidence bounds) for function (9) are: a = -1.968⋅10 5 (or alternatively -1.731⋅10 14 , 1.731⋅10 14 ), b = -0.001531 (or -131.3, 131.3), c = 1.968⋅10 5 (or alternatively -1.731⋅10 14 , 1.731⋅10 14…”
Section: Resultsmentioning
confidence: 99%
“…An electronically controlled engine simulated to validate the model was found to be capable of predicting NOx emissions and specific fuel oil consumption with 95 % confidence intervals. However, Larsenb et al (Larsenb et al, 2015) study looked into two-stroke diesel machinery for ships, with five varying configurations to explore the trade-off between increased NOx emissions and reduction in fuel consumption. By implementing a waste heat recovery system using an organic Rankine cycle and a hybrid turbocharger, fuel consumption decreased by up to 9 % and NOx up to 6.5 %.…”
Section: Introductionmentioning
confidence: 99%
“…The low performance at low engine loads is a consequence of the low exhaust gas temperatures. The combined performance of the diesel engine and the WHR system can be optimized by considering the simultaneous optimization of engine tuning and WHR system design [17]. Diesel engines supplied with selective catalytic reduction (SCR) employ a special tuning enabling high temperatures at low engine loads, which is required for the operation of the SCR system [62].…”
Section: Process Characteristics and Integrationmentioning
confidence: 99%
“…This point was highlighted by Baldi et al [16] who demonstrated the importance of accounting for variations in ship operation, when optimizing a marine machinery system. Larsen et al [17] studied the NO x emission and specific fuel oil consumption (SFOC) trade-off for a large marine diesel engine equipped with an ORC bottoming cycle unit while accounting for off-design operation. A combined optimization of the diesel engine, hybrid turbocharger and ORC system yielded NO x emission reductions of 6.5% and SFOC reductions up to 9%.…”
Section: Introductionmentioning
confidence: 99%